2019
DOI: 10.1177/1129729819851059
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular catheter migration: A cross-sectional and health-economic comparison of adhesive and subcutaneous engineered stabilisation devices for intravascular device securement

Abstract: The Infusional Services Team at a large cancer centre in Belfast, Northern Ireland, performed a cross-sectional analysis of two catheter securement technologies to address an area of frequent, but underestimated concern – peripherally inserted central catheter migration and dislodgement. Healthcare practitioner and patient feedback, along with economic impact, were assessed. The costs associated with catheter replacement during the adhesive device group study period were calculated using an average cost per in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…An additional paper, 9 published online during the revision of the present document, was later forwarded to the panelists. Answers from the individual experts on each specific question were combined together in a narrative form, leading to a number of final statements with a proper degree of Consensus from the whole working group.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…An additional paper, 9 published online during the revision of the present document, was later forwarded to the panelists. Answers from the individual experts on each specific question were combined together in a narrative form, leading to a number of final statements with a proper degree of Consensus from the whole working group.…”
Section: Methodsmentioning
confidence: 99%
“…Another bias of the few published studies is the very small number of patients (in most cases, 30-50) in each trial. However, at the time of the revision of the present document, a new clinical study was published 9 -a prospective observational study with a retrospective control groupwhere SAS was used in more than 1000 patients, with maximal efficacy (no dislodgment). The results of this large study are consistent with the results of all the clinical studies on SAS which have been published or presented in international conferences as posters or oral presentations in the last few years.…”
Section: Part 1: the Use Of Subcutaneously Anchored Sutureless Systems For Securement Of Vads In Adult Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by McParlan found the use of SESDs provided an average cost savings per patient (€81.92/US$93.41), lower complications, and served as a safe and affordable alternative to PICC securement. 30 Financial savings by mitigating the risks of CLABSIs are additionally a benefit to the economic health care burden. Performing CER at all levels benefit the patient population for increasing transferability of practice with theoretical, practical, and future implications to practice.…”
Section: Discussionmentioning
confidence: 99%